The Sercmknre and Music in Tlokweng, Botswana, by Jürgen Schöpf, Intercultural Music Studies 13, edited by Max Peter Baumann, Institute for Music Research, Julius- Maximilian University of Würzburg, Verlag für Wissenschaft und Bildung, Berlin 2008, 279 pp., 108 pp. of music transcriptions, 5 photographs and 13-track DVD, 9783-86135-645-5. - Tracey, Andrew (International Library of African Music, 2009)
pages: 162-163
Keywords: Music; African Music; Botswana; Music Research